Hemoglobinopathies & Types: Overview, Pathophysiology, and Epidemiology - Khandaker, Musomi; Ferdouse, Rafsana; Shemu, Amena Akter (Journal of Medicine and Health Sciences Research, 2025)
The hemoglobinopathies encompass all genetic diseases of hemoglobin. They fall into two main groups: thalassemia syndromes and structural hemoglobin variants (abnormal hemoglobins). α- and β-thalassemia are the main types of thalassemia; the main structural hemoglobin variants are HbS, HbE, and HbC. There are many subtypes and combined types in each group. The highly variable clinical manifestations of the hemoglobinopathies range from mild hypochromic anemia to moderate hematological disease to severe, lifelong, transfusion-dependent anemia with multiorgan involvement. According to the World Health Organization, about 5.2% of the world population and over 7% of pregnant women carry a significant variant, and 1.1% of couples worldwide are at risk of having children with a hemoglobin disorder. This review will explain the overview, pathophysiology, and epidemiologic scenarios of each hemoglobinopathy, the information of which will be useful for those who are working and interested in the following field.